Penggunaan Game Edukatif Berbasis Android Dalam Meningkatkan Hasil Belajar Matematika - Annekarela (CV. SINAR HOWUHOWU, 2025)
This study aims to examine the effectiveness of using Android-based educational games in improving mathematics learning outcomes among elementary school students. The research employed a quasi-experimental method with a Nonequivalent Control Group Design. The subjects consisted of two fifth-grade classes at an elementary school in Yogyakarta: an experimental class that used educational games and a control class that received conventional instruction. Research instruments included a mathematics achievement test, student activity observation sheets, and a student response questionnaire. The results revealed a significant difference in learning outcomes between the two groups, with the experimental group achieving a higher average score. Furthermore, students who used educational games showed greater motivation, engagement, and conceptual understanding. These findings suggest that Android-based educational games are an effective, engaging, and relevant learning medium for the digital-native generation.